Review article: The meristem in indeterminate root nodules of Faboideae - Łotocka, Barbara (Springer Netherlands, 2013)
In this review, the anatomy of indeterminate legume root nodule is briefly summarized. Next, the indeterminate nodule meristem activity, organization and cell ultrastructure are described in species with a distinct nodule meristem zonation. Finally, the putative primary endogenous factors controlling nodule meristem maintenance are discussed in the context of the well-studied root apical meristem (RAM) of Arabidopsis thaliana.